'Sick and tired': Patients reported reasons for not participating in clinical psychiatric research. (11th October 2019) - Bixo, Liv; Cunningham, Janet L.; Ekselius, Lisa; Öster, Caisa; Ramklint, Mia
Abstract: Background: Meaningful and generalizable research depends on patients' willingness to participate. Studies often fail to reach satisfactory representativeness. Objective: This paper aims to investigate reasons for not participating in research among young adult patients with psychiatric illness. Method: A quantitative cross‐sectional study was performed based on questionnaires reported on by 51 psychiatric patients (14 males, 35 females and two unspecified) who had previously declined participation in an ongoing research project. Thereafter, a qualitative interview with subsequent content analysis was conducted with ten additional patients (five males, five females). Results: The questionnaires indicate being 'too tired/too sick to participate' as the most common barrier. Lack of time and fear of needles were other common barriers. Lack of trust or belief in the value of research was less inhibitive. In the interviews, disabling psychiatric symptoms were confirmed as the main reason for not participating. Several potential ways to increase participation were identified, such as simplification of procedures and information as well as providing rewards and feedback, and building relationships before asking. Conclusion: This study is unusual as it focuses on the group of young people attending psychiatry outpatient clinics we know very little about – those who do not partake in research. Our results indicate that fatigue and sickness reduce research participation and identify factors that may facilitate enrolment of this important group.